Tinjauan Kondisi Fisik Wasit Sepak Bola Pengcab PSSI Kota Lubuklinggau - Azizil Fikri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
The purpose of the study is to know the football referee physical condition of PSSI commitee in Lubuklinggau. The population of the study is fifteen football referees who live in Lubuklinggau and approved by PSSI committe of Lubuklinggau city. Total sampling is used because of limited population, therefore all the population (15 people) is taken as sample. Based on data analysis by using SPSS 12 version showed that sig. 0.918 > 0.05, therefore the data of referee endurance is normal distribution. The referee speed is in good category which the mean score is 4 (40%). Based on data analysis, sig. 0.927 > 0.05. Therefore the data of referee speed is normal distribution. Referee speed is in very good category with the mean score 5 (60%). Based on data analysis, referee speed is normal distrubution sig. 0.761 > 0.05. Ins summary, football referee endurance and speed of CI committee lubuklinggau city is in good category. Meanwhile football referee endurance of CII is in low category and football referee speed of CII is in good category. Keyword: Durability, Speed, Referee